Interventions for Pedohebephilic Arousal in Men Convicted for Sexual Offenses Against Children: A Meta-Analytic Review - Mcphail, Ian V. (Criminal justice and behavior, 2020)
Given the centrality of pedohebephilic interest in understanding sexual offending against children, several interventions have been developed to help men manage or inhibit their sexual arousal to children to reduce the intensity of their experience of such arousal. A meta-analytic review was conducted to examine the effectiveness of interventions for managing pedohebephilic arousal, as measured by phallometric testing. A systematic literature review identified 23 within-group design studies and 18 single-case design studies (N = 1,071) for analysis. Behavioral and pharmacological interventions showed moderate to large effects for reducing pedohebephilic arousal. Moderator analyses suggest that men with high pretreatment pedohebephilic arousal showed the greatest reductions in arousal. Small effects were found for comprehensive treatment programs; none of the interventions had the effect of increasing sexual arousal to adults. These results support the effectiveness of behavioral and pharmacological interventions for managing pedohebephilic arousal in men convicted of sexual offenses against children.